7th International Workshop on Osteoarthritis Imaging report: "imaging in OA – now is the time to move ahead". Issue 6 (June 2015) - Guermazi, A.; Eckstein, F.; Hunter, D.; Roemer, F.
Summary: The 7th Osteoarthritis Research Society International (OARSI) International Workshop on Osteoarthritis Imaging was held in Reykjavik, Iceland, from July 9–12, 2014; attracting attendees from academia, pharmaceutical and Magnetic resonance imaging (MRI) industries, as well as a large number of young investigators. The Workshop program consisted of six modules, including imaging in osteoarthritis (OA), imaging and pain in OA, new techniques in imaging, risk factors and structural outcomes, anti-nerve growth factor (a-NGF) therapy, and joint replacement. A wealth of data was presented from OA researchers from all over the world and participants gained insightful knowledge on up-to-date research work focusing on imaging of OA. This paper presents a summary of the salient points from the workshop. Conclusions: Identifying the appropriate imaging modality and parameters will be critical for ensuring responsive, reproducible and reliable outcomes for clinical trials. Continued efforts from the OA research community are needed to establish the most effective use of imaging in OA clinical trials, including anti-NGF therapy and joint replacement trials, and to validate newer imaging techniques such as compositional MRI for use in the future clinical trials.